The Role of Government Spending in Developing the Productive Capacity of The Iraqi Economy - Muhammad Abdul-Ameer Atiyah Al-Yasi,; Harith Rahim Atiyah Al-Yasi, (Technium Social Sciences Journal, 2024)
The research seeks to demonstrate the impact of government spending on the productive capacity of the Iraqi economy, as the continuous increase in the volume of public spending and the adoption of the planned deficit method in the budgets of various years must reflect positively on the productive capacity of the country, so the relationship between the two variables was estimated according to the autoregressive distributed lag model ( ARDL) as it shows the relationship in the short and long terms and for the period 2004-2022, and among the results obtained is that current spending has a negative impact on the productive capacity index. This means that current spending is unproductive within its vicious circle, that is, money leaks out without generating economic returns for the country. Investment spending has a positive impact on the productive capacity index, as the average investment spending during the research period amounted to approximately (20%) of government spending, which is a very low percentage that was reflected in the weakness of the investment-based structures of the Iraqi economy, and this is what made the productive capacity index of the Iraqi economy It records a low percentage, reaching its best levels (35%), and this is consistent with the weak allocation of financial resources in investment aspects. What supports the analysis is the relationship test, which shows us that investment spending has a positive and significant effect on production capacity, but its parameter reached (0.07), which is a very low percentage. It has almost no effect. However, if a large percentage of financial resources were directed towards investment areas, this would develop projects, increase their ability to produce and productivity, and achieve high rates of GDP growth. Therefore, the research recommends the necessity of directing government spending towards productive sectors in order to improve production capabilities and achieve sustainable development comparable to developed countries, as well as periodically monitoring and evaluating the extent of the productivity of public spending in various economic sectors in order to make it more effective.